Plinabulin, a Distinct Microtubule-Targeting Chemotherapy, Promotes M1-Like Macrophage Polarization and Anti-tumor Immunity - Natoli, Marina; Herzig, Petra; Pishali Bejestani, Elham; Buchi, Melanie; Ritschard, Reto; Lloyd, G. Kenneth; Mohanlal, Ramon; Tonra, James R.; Huang, Lan; Heinzelmann, Viola; Trüb, Marta; Zippelius, Alfred; et al. (Frontiers in Oncology, 2021)
Reprogramming tumor infiltrating myeloid cells to elicit pro-inflammatory responses is an exciting therapeutic maneouver to improve anti-tumor responses. We recently demonstrated that a distinct microtubule-targeting drug, plinabulin - a clinical-stage novel agent - modulates dendritic cell maturation and enhances anti-tumor immunity. Here, we investigated the effects of plinabulin on macrophage polarization in vitro and in vivo. Plinabulin monotherapy induced significant tumor growth inhibition in mice bearing subcutaneous MC38 colon cancer. Importantly, the regressing tumors were characterised by an increase in M1-like/M2-like tumor-associated macrophages (TAM) ratio. The efficacy of plinabulin remained unaltered in T cell-deficient Rag2-/- mice, suggesting an important role of macrophages in driving the drug’s anti-tumor effect. Exposure of plinabulin to murine and healthy human macrophages induced polarization towards the M1 phenotype, including increased expression of co-stimulatory molecules CD80, CD86 and pro-inflammatory cytokines IL-1β, IL-6 and IL-12. M2-associated immunosuppressive cytokines IL-10 and IL-4 were reduced. This pro-inflammatory M1-like skewing of TAMs in response to plinabulin was dependent on the JNK pathway. Functionally, plinabulin-polarized human M1 macrophages directly killed HuT 78 tumor cells in vitro. Importantly, plinabulin induced a functional M1-like polarization of tumor infiltrating macrophages in murine tumors as well as in tumor samples from ovarian cancer patients, by preferentially triggering M1 proliferation. Our study uncovers a novel immunomodulatory effect of plinabulin in directly triggering M1 polarization and proliferation as well as promoting TAM anti-tumoral effector functions.